Animal Genetic Resources in the IGAD Region: Regional Policy Brief on Policy and Legal Issues - The IGAD Center for Pastoral Areas and Livestock Development (ICPALD) (The IGAD Center for Pastoral Areas and Livestock Development (ICPALD), 2019)
The Intergovernmental Authority on Development (IGAD) is a regional economic community in the horn of Africa. Its member state comprises Uganda, Sudan, South Sudan, Somalia, Kenya, Ethiopia, Eritrea and Djibouti stretching over an area of 5.2 million km². IGAD has three priority areas of focus namely a) food security and environmental protection; (b) economic cooperation, regional integration and social development; and (c) peace, security and humanitarian affairs.